CALCULATION OF 3-D SURFACE CRACK STRESS INTENSITY FACTOR BASED ON APDL AND UIDL - CHE FuYan; GENG LiMing (Jixie qiangdu)
In engineering,cracks are usually regarded as semi-elliptical surface cracks. It is not easy to establish a complete finite element model of a semi-elliptical surface crack,thus a quarter of the crack model is generally used to calculate the stress intensity factor by finite element method. This paper adopts APDL and UIDL technologies for secondary development of ANSYS software,establishes a complete model of semi-elliptical surface crack by simple interface operation with the method of model block processing. Using this method,the stress intensity factors of the central semi-elliptical crack and the oblique semielliptical crack were solved respectively. The results are basically consistent with the theoretical solution and the results in the literature,which shows that it is accurate and reliable to use the complete crack model established by this method to calculate the stress intensity factor. The combined development modeling function can be used to solve the stress intensity factors in complex structures under complex loads,and has important value for practical application of engineering.